Buzzer as the Driving Force for Buzz Marketing on Twitter in the 2019 Indonesian Presidential Election - Handini, Virgia Aida; Dunan, Amri (Publisher Cv. Inara, 2021)
This study aims to determine Buzzers' existence and the Buzz Marketing strategy carried out by Buzzers during the 2019 Presidential Election on Twitter. The method in this study used qualitative research with Sostac P.R Smith's analysis. As a result, 1) the Buzzer's existence in the 2019 Indonesian Presidential Election contest was formed at the end of 2018. The formation of a Professional Buzzer was carried out through a recruitment process held by several legal companies with a predetermined payment system; 2) In carrying out Buzz marketing, Buzzer has arranged plans to distribute political content. Buzzers use a variety of political strategies to amplify political messages. Then, the political messages are spread using a minimum of three or more accounts to engage in a conversation. Through systematic Buzz marketing planning, political messages that are informative, persuasive, and instructive systematically and intensely to Twitter netizens make the results more optimal. However, Buzzer still needs to formulate political content that is more attractive to Twitter netizens, such as avoiding old content that uses political narratives containing SARA elements, hoaxes, hate speech, and other propaganda.